Patriarchy and progressive politics: gendered resistance to mining through everyday social relations of state formation in Intag, Ecuador. Issue 1 (March 2020) - Billo, Emily
Over the last decade, the Ecuadorian government, following regional trends, called for social and environmental progress through state-controlled resource extraction. Scholars have demonstrated that this neo-extractive model warranted further investigation regarding its progressive aims. Specifically, this paper examines gendered critiques of state-led extractivism linked to expanding governmental and social programs. Even as women asserted their political recognition and rights in state politics, they still confronted patriarchal relations in their everyday lives. Drawing on eight months of ethnographic research over 6 years in campesino communities of Junín and Chalguayacu Alto, I argue that women in Intag challenged patriarchal state relations of extractive capitalism. This paper offers a novel contribution to literature on neo-extractivism and gendered forms of resistance. Women held the state accountable for its promises of social welfare and infrastructural development through which it generated public support for controversial mineral projects. These symbols of state paternalism revealed expanded patriarchal structures that underpinned their daily lives, with significance for a gendered politics of resistance.